1995
DOI: 10.1002/ptr.2650090508
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of diosquinone and plumbagin from the root of Diospyros mespiliformis (Hostch) (Ebenaceae)

Abstract: Diosquinone and plumbagin isolated from the root of Diospyros rnespiliforrnis (Hostch), a common ingredient in several folk medicines and foods, have been shown to have antibacterial activity against a wide range of organisms. The minimum inhibitory concentrations (MICs) of diosquinone against Staphylococcus aureus NCTC 6571 and S. aureus E3T ranged from 3 to 30 pglmL, while those against Escherichia coli KL16 and Pseudomoms aeruginosa NCTC 6750 ranged from 15 to 16pglmL. MICs were found to increase with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…The minimum inhibitory concentration (MIC) of the methanol leaf extract of E. camaldulensis, ceftriaxone and gentamycin were carried out using the agar dilution method described by Lajubutu et al, (1995). Different concentrations were prepared to give a final 50 to 0.048 mg /ml, 2500 to19.5 µg/ml, 2000 to1.95 µg/ml of the plant extracts, ceftriaxone (CRO), gentamycin (CN), respectively.…”
Section: Minimum Inhibitory Concentrations Of Ceftriaxone Gentamycinmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) of the methanol leaf extract of E. camaldulensis, ceftriaxone and gentamycin were carried out using the agar dilution method described by Lajubutu et al, (1995). Different concentrations were prepared to give a final 50 to 0.048 mg /ml, 2500 to19.5 µg/ml, 2000 to1.95 µg/ml of the plant extracts, ceftriaxone (CRO), gentamycin (CN), respectively.…”
Section: Minimum Inhibitory Concentrations Of Ceftriaxone Gentamycinmentioning
confidence: 99%
“…Tested Compound: Diosquinone[1], a naphthoquinone epoxide which we have previously isolated from the root sample of D. mespiliformis (collected from Olokemeji forest reserve in Ogun state of Nigeria during the onset of raining season) (Lajubutu et al, 1995) and the root of D. tricolor (collected from coastal area of Lagos State) (Lajubutu, 1994) was used in this assay.…”
Section: Methodsmentioning
confidence: 99%
“…This is the first known report of the cytotoxicity potential of diosquinone. This compound which has been reportedly isolated and identified from two Nigerian Diospyros species (Lajubutu 1994, Lajubutu et al, 1995 has only been documented for its antibacterial activities.…”
Section: B a Adeniyi Et Almentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have shown that the leaf extracts of D. mespiliformis are effective against Plasmodium falciparum in vitro (Etkin, 1997), Plasmodium berghei invivo (Adzu and Salawu, 2009) and relieved pains and fever in rodent models (Adzu et al, 2002). Tannins, alkaloids, diosquinone and plumbagin were isolated from D. mespiliformis and demonstrated activity against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa thus providing the basis for the plant usage in herbal medicine (Adeniyi et al, 2006;Lajubutu et al, 2006). Root extract of D. mespiliformis have shown toxicity potential using subchronic administration in mice (Ali et al, 2012).…”
Section: Introductionmentioning
confidence: 99%